Statistical Evaluation of Chronic Apical Periodontitis and Radicular Cysts - Baghaei-Naeini F; Hajloo R (Tehran University of Medical Sciences, 2000)
Up to now, no complete study was carried out about the prevalence and location of periapical granuloma and radicular cysts from the point of view of clinical symptoms (e.g. pain and swelling fistula) in Iran. The data was collected from the files available in the Department of Pathology, faculty of Dentistry, Tehran University of Medical Sciences. With a consideration on different therapeutic methods. a proper method was selected. Radicular cyst occurred in 59.3 percent of 324 cases while 45.7 percent were granuloma. The most common incidence of these lesions was in the range of 24-25 years old. The most common location of lesions was the maxillary anterior. Sinus tracts occurred in 74 of all cases. 47.3 percent of these patients have been previously received root canal therapy. It is noticeable that 24 percent of all patients were treated endodontically before surgery. Higher incidence of granuloma occurred in small lesions while cysts were more common in large lesions. 232 of all cases showed one of the clinical symptoms, 16% pain, 35.8% swelling and 22.8% fistula. No symptoms were found in 92 cases.